Benchmarking animal handling outcomes and analyzing impacting factors on cow-calf operations - Calaba, Elaine, author; Edwards-Callaway, Lily, advisor; Hess, Ann, committee member; Engle, Terry, committee member; Ahola, Jason, committee member (Colorado State University. Libraries, 2022)
Animal handling is an important part of the cattle industry; proper handling of animals can improve animal welfare and increase consumer confidence. One way handling is assessed on cow-calf operations is through producer education programs, such as the Beef Quality Assurance (BQA) program. A part of these producer education programs is assessing animal handling outcomes. However, there has not been much research into the occurrence and implication of cow handling outcomes. The objectives of this study were to: 1) quantify handling outcomes on cow-calf operations in the United States and 2) investigate potential factors that may influence these outcomes. An assessment was developed by refining existing BQA Cow-Calf program outcome definitions in addition to questions about animal factors, facilities, and management factors. Handling outcomes observed included: Prod Use, Miscatch, Vocalization, Jump, Slip/Stumble, Fall and Run. A total of 76 cow-calf operations were sampled in 24 states (Central, n = 17; East, n = 30; West, n = 29), with herd sizes ranging from 10 head to more than 5,000 head. Observations occurred during processing of either cows or yearling heifers through a cattle chute restraint system, regardless of procedure being performed. With herds less than 100 head, all cows or yearling heifers were observed as they moved through the single file alley, into the chute, and upon exiting the chute for a distance of three body lengths. On operations greater than 100 head, a maximum of 100 contiguous head were observed. Results indicate that most participants were BQA trained (70%) and had crossbred herds (63%) with a Docile temperament (57%) and had Daily Visual Contact with their herds (47%). The mean observations for Prod Use (18.1% ± 28.9), Miscatch (2.5% ± 5.1), and Fall (2.5% ± 4.2) exceeded the upper limit of BQA standards. The BQA threshold for Prod Use is 10%, Miscatch is 0%, and Fall is 2%. Vocalization (3.8% ± 7.6), Jump (7.5% ± 9.9), Run (7.7% ± 13.8), and Slip/Stumble (6.3% ± 9.1) were within BQA thresholds (5%, 25%, and 10% respectively). Prod Use had the greatest number of impacting factors including BQA status, Herd Size Group, Temperament, and Visual Contact while Miscatch, Vocalization, and Fall all had single impacting factors (Region, Temperament, Visual Contact, respectively). Visual Contact and Temperament had an association with the majority of outcomes. Future research should focus more in-depth on specific factors and the variety contained within and on the role of veterinarians in handling outcome frequencies.
Keywords: beef quality assurance; animal welfare; handling outcomes